Discovery and follow-up of ASASSN-19dj: an X-ray and UV luminous TDE in an extreme post-starburst galaxy. Issue 2 (15th October 2020) - Hinkle, Jason T; Holoien, T W-S; Auchettl, K; Shappee, B J; Neustadt, J M M; Payne, A V; Brown, J S; Kochanek, C S; Stanek, K Z; Graham, M J; Tucker, M A; Do, A; et al.
ABSTRACT: We present observations of ASASSN-19dj, a nearby tidal disruption event (TDE) discovered in the post-starburst galaxy KUG 0810+227 by the All-Sky Automated Survey for Supernovae (ASAS-SN) at a distance of d ≃ 98 Mpc. We observed ASASSN-19dj from −21 to 392 d relative to peak ultraviolet (UV)/optical emission using high-cadence, multiwavelength spectroscopy and photometry. From the ASAS-SN g -band data, we determine that the TDE began to brighten on 2019 February 6.8 and for the first 16 d the rise was consistent with a flux ∝ t 2 power law. ASASSN-19dj peaked in the UV/optical on 2019 March 6.5 (MJD = 58548.5) at a bolometric luminosity of L = (6.2 ± 0.2) × 10 44 erg s −1 . Initially remaining roughly constant in X-rays and slowly fading in the UV/optical, the X-ray flux increased by over an order of magnitude ∼225 d after peak, resulting from the expansion of the X-ray emitting region. The late-time X-ray emission is well fitted by a blackbody with an effective radius of ∼1 × 10 12 cm and a temperature of ∼6 × 10 5 K. The X-ray hardness ratio becomes softer after brightening and then returns to a harder state as the X-rays fade. Analysis of Catalina Real-Time Transient Survey images reveals a nuclear outburst roughly 14.5 yr earlier with a smooth decline and a luminosity of LV ≥ 1.4 × 10 43 erg s −1, although the nature of the flare is unknown. ASASSN-19dj occurred in the most extreme post-starburst galaxy yet to host a TDE, with Lick Hδ A = 7.67 ± 0.17 Å.